TANGGUNG JAWAB HUKUM PELAKU USAHA ATAS PEMBERIAN KOMPENSASI KERUGIAN KONSUMEN DALAM LAYANAN OPEN TRIP OLEH SAHABAT RATU TOUR AND TRAVEL DI SURABAYA - Aulia Rahmah Dwiyanti; Miko Aditiya Suharto (Jurnal Ilmiah Advokasi, 2026)
Open Trip, as an innovation in the tourism industry, offers convenience for travelers but also creates potential disputes due to discrepancies between services provided and contractual agreements. This study aims to analyze the implementation of consumer compensation mechanisms in Open Trip services organized by Sahabat Ratu Tour and Travel in Surabaya. This research employs an empirical juridical method with a descriptive-prescriptive approach, as well as structural and conflict approaches. Data were collected through questionnaires distributed to consumers, interviews with service providers, and literature review of the Indonesian Civil Code, Consumer Protection Law, and Tourism Law. The findings indicate that, normatively, consumers are entitled to compensation for losses as stipulated under the Consumer Protection Law and the Tourism Law. However, in practice, the implementation of compensation remains suboptimal. This is reflected in the ineffective enforcement of business liability mechanisms, the weak bargaining position of consumers in standard form contracts, and the limited supervision of third-party involvement. In addition, low legal awareness and the tendency of consumers to refrain from pursuing legal remedies further hinder the realization of compensation rights. This study highlights that the application of the principles of liability and good faith in contractual relationships is essential to strengthening consumer protection. Therefore, it is necessary to reinforce legal mechanisms for compensation, enhance regulatory supervision, and improve consumer legal awareness in order to establish a more effective and equitable protection system within the tourism industry.Keywords: Consumer Protection; Compensation; Open Trip; Tourism